FABRICATION AND ANALYSIS OF A SOLAR-POWERED SPRAYER WITH VARIOUS USES FOR AGRICULTURE (International Journal of Food and Nutritional Sciences, 2023)
The agricultural pesticide sprayer that is the subject of this innovation is powered by solar energy. The device is comprised of a 20-watt solar panel, a 12-volt DC battery that is charged by solar radiation captured by the panel, a DC motor that runs on the battery power, a pump that applies pesticide, and a tank that stores the pesticide (in liquid or solution form). The equipment may be operated by a single laborer and is fully portable. Sprayer discharge rates were measured in both laboratory and outdoor settings; the average discharge rate was roughly the same in both, averaging 0.023 l/s (82.8 l/h) in both scenarios. The sprayer's performance was assessed when it was being used to spray various crops in farmer's fields, including cotton, green gram, onions, and so forth. With the operator walking at approximately 2.8 km/h and the sprayer's swath width of 0.6 m, the theoretical field capacity is approximately 0.17 hectares per hour. The sprayer's effective field capacity was found to be 0.14 ha/h, or an average coverage of 1 ha per day during an 8-hour operation. Because the equipment is operated by the user and doesn't rely on any other external power source, it decreases manual labor and is both cost-effective and environmentally benign. Small and marginal farmers can easily afford the solar energy it consumes. Its electricity can also be utilized for multiple purposes, like as lighting up the house, charging a mobile device's battery, and running a radio, making it a more commercially feasible technology.